Assessment of Renewable Energy Potential in Building Integrated System for High Rise Building - Swe Zin Oo; Swe, Wunna (The Indonesian Journal of Computer Science, 2025)
This research presents the design form the renewable energy sources from the high -rise building, ICON Mandalay in Mandalay,Myanmar. The amount of renewable energy sources that can be harnessed from Building Integrated Photovoltaic (BIPV)panels installed the four facades of the high-rise building and presents the ideas of designing a small-sized wind turbine or micro wind turbine for high rise structure to generate electricity was estimated. The energy self-sufficiency of high- rise building can be approached by generating the renewable energy sources without effecting the original purpose of the structures. As global energy consumption continues to rise, managing building energy use through on-site renewable energy generation can help meet this growing demand. Based on the available building area, calculations show that the two renewable energy sources can be installed, allowing for significant energy generation potential. This paper study energy generation from building integrated renewable energy sources under varying conditions, providing insight into the variability and reliability of energy production in such an environment. Additionally, the total available energy from the BIPV is estimated 5.878 MWh/Day and micro wind Turbines is generated 43.662 kWh/Day and potential contribution to the building's power demands of high-rise buildings. The finding that the amount of energy generated by BIPV in high-rise building is 134 times grater than the energy generated by micro wind power. Therefore, BIPV sources are the most convenient option for urban energy generation in high-rise building.